Ethnobotanical study of the cultural value and preservation status of adansonia digitata (baobab species) among Vhavenda of Sagole Community in the LImpopo Province - Mathaba, Matsheremane Godfry (University of Limpopo, 2016)
The baobab tree (Adansonia digitata), with more than 300 cultural and ethnobotanical uses in Africa has been identified as one of the most important savanna trees to be conserved, domesticated and valorised on the continent. A decline in baobab populations due to overexploitation could have a significant negative effect on African livelihoods. Therefore, it is important to determine potential strategies for the conservation of this tree species. The study aimed to explore the cultural significance and ethnobotanical use, as well as conservation of baobab trees by the Sagole community in the Vhembe District of the Limpopo Province, South Africa. Furthermore, the conservation efforts of this community and the provincial government were also elucidated. In the Sagole community 40 local community members, aged 20 years and older, were selected via convenience sampling. A semi-structured questionnaire was employed to collect information on the cultural significance of baobab trees to members of this community. Research questions focussed specifically on identifying folk taxonomy, the transfer of species-specific information to younger generations, and cultural taboos pertaining to the baobab. It has been discovered that young people of Sagole are not well versed in the cultural value pertaining to baobabs. Furthermore, members of the community and the village head (chief) have limited knowledge related to taboos associated with this species. Thus, when individuals transgressed a taboo related to this tree species there is no formal punishment. Sagole community members use baobab trees for various purposes such as food and medicine. The species is used medically to cure various ailments. Most inhabitants in the community harvest this tree. The most common plant parts harvested for cultural use are the fruits, bark, roots and leaves. However, community members have limited knowledge about the taboos related to harvesting of this majestic tree.
Thesis (M. A. (Anthropology)) -- University of Limpopo, 2016
Keywords: Baobab tree; Conservation of Baobab trees; Adansonia digitata; Plants -- Folklore; Sagole Community of Venda -- Ethnobotany